PERKECAMBAHAN BENIH DAN PERTUMBUHAN SEMAI TANJUNG (Mimusops elengi L.) PADA BERBAGAI TEKNIK SKARIFIKASI DAN MEDIA TUMBUH - Haranti, Mefa; Wardah, Wardah; Yusran, Yusran (Jurnal Warta Rimba, 2017)
Cape (Mimusops elengi L.) treeis one of tree species that grows quickly and adapts easily in tropical area. But, the cape tree needs a longer time to get germination becuase of its hard seed skin. Therefore, it needs scarification or earlier treatment in order to fasten the seed germination. The objective of the reseach was to find out both of seed germination and seedling growth of the cape tree (Mimusops elengi L) on some scarification techniques and growing medium. The research was conducted on June to August 2015 in Permanent Seedling of BPDAS Palu – Poso, Tadulako University, Palu. The soil analysis was conducted in Agronomy Laboratory, Forestry Faculty, Tadulako University. The research applied Factorial Pattern of Complete Randomized Design that consisted of 2 factors and repeated 5 times. The first factor was scarification technique that without scarification or control (S0), seed was submerged in cool water for 3x24 hours (S1), submerged in hot water with early temperature 100°C for 15 minutes (S2), and it submerged with KNO3 0,5% for 10 hours (S3). The second factor was growing medium, soil (M0) and soil mixed with hull of rice charcoal (M1), so there were 8 treatments combination, they were S0M0, S0M1, S1M0, S1M1, S2M0, S2M1, S3M0, and S3M1. The result of the research showed that treatment combination of seed scarification that submerged with KNO3 0,5 % for 10 hours by using soil growing medium (S3M0) gave the highest result on percentage parameter of seed germination of 81,1%, the speed of germinationwas 25,44 days, and seedling wet weight was 0,562 gram. The treatment combination of seed that submerged in cool water for 3x24 hours by using growing medium soil mixed with hull of rice (S1M1) gave the highest result on the parameter length of seedling rootwas 9,4 cm.Keywords : Cape tree(Mimusops elengi L.), Scarification, Seed, Growing Medium